Additional file 14 of STING pathway contributes to the prognosis of hepatocellular carcinoma and identification of prognostic gene signatures correlated to tumor microenvironment - Zhangya Pu; Jinghua Liu; Zelong Liu; Fang Peng; Yuanyuan Zhu; Xiaofang Wang; Jiayan He; Panpan Yi; Xingwang Hu; Xuegong Fan; Jiang Chen (figshare, 2022)
Additional file 14: Figure S10. The relationship between transcriptional expression of VAV1 (A), RHOA (B), and ZC3HAV1 (C) and the infiltration of immune cell subtypes in three independent single-cell sequencing HCC datasets from TISCH database. TISCH: Tumor Immune Single-cell Hub.
Keywords: Immunology